PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DIVISI KURIR STUDI PADA J&T EXPRESS GARUT 01 (PT. GLOBAL JET EXPRESS) - tita rachtawati santanu; Amaliyah Fira Madhani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is motivated by the performance of employees at J&T Express Garut 01 (PT. Global Jet Express) which is categorized as not optimal because there are still many influencing factors. The purpose of this study was to determine the effect of work stress and workload on the performance of the study courier division employees at J&T Express Garut 01 (PT. Global Jet Express) partially and simultaneously. The research method used is a quantitative method with a descriptive and associative approach. The population is 33 couriers (sales), all of which are used as saturated samples. Based on the simple correlation test analysis, the effect of work stress variable (X1) on employee performance (Y) has a strong/close relationship that is equal to r = 0.622. From the simple correlation test, the effect of the workload variable (X2) on employee performance (Y) has a fairly strong/close enough relationship that is equal to r = 0.548. From the multiple correlation test, the effect of work stress (X1) and workload (X2) on employee performance (Y) has a fairly strong/close enough relationship that is equal to r = 0.591. The coefficient of determination test or R square is 0.420, which means that 42% of employee performance variables can be influenced by work stress and workload variables